Formation of catalytically active copper and nickel nanoparticles in natural zeolites; 4th FEZA Conference, Collège de France, Paris, France, september, 2-6, 2008 - Petranovskii V.; Pestryakov A. N. Aleksey Nikolaevich; Kazantseva L. K.; Cruz J.; Kryazhov A. N. (2008, 2008)
Structure, thermostability and catalytic properties of copper and nickel nanoparticles in natural and synthetic zeolites have been studied using methods of XRD, elemental analysis, UV-visible spectroscopy, MAS NMR, TEM and catalytic testing. Different states of Cu have been identified by UV-Vis spectroscopy: Cu+ and Cu2+ ions, O-Cu-O and Cu-O-Cu complexes and Cu nanoparticles. Measurements of synthetic zeolites showed that shape and position of plasma resonance band depend on the acidity of zeolite supports. The most acid mordenites with Si/Al≈7-10 prevents formation of copper nanoparticles while Cu2+ is reduced to Cu+ and few atomic Cun clusters. Less acid erionite, clinoptilolite and mordenites with high Si/Al ratio promote formation of Cu nanoparticles. For Ni-exchanged zeolites spectra typical for Ni(H2O)62+ are observed. The spectra changed with increasing temperature due to dehydration of Ni2+ coordination sphere and replacement of H2O ligand molecules by oxygen atoms of zeolite framework. The catalytic experiments demonstrate that the temperature of beginning of hydrocarbons conversion starts in 170-250°C range, depending on the composition of the catalyst. The complete conversion can be observed for all zeolites, depending (probably) on Si/Al ratio of the zeolite matrix. No destruction of crystalline structure was observed from XRD and 27Al MAS NMR spectra under conditions used for catalytic tests.